A calmodulin‐like protein regulates plasmodesmal closure during bacterial immune responses. Issue 1 (17th May 2017) - Xu, Bo; Cheval, Cécilia; Laohavisit, Anuphon; Hocking, Bradleigh; Chiasson, David; Olsson, Tjelvar S. G.; Shirasu, Ken; Faulkner, Christine; Gilliham, Matthew
Summary: Plants sense microbial signatures via activation of pattern recognition receptors (PPRs), which trigger a range of cellular defences. One response is the closure of plasmodesmata, which reduces symplastic connectivity and the capacity for direct molecular exchange between host cells. Plasmodesmal flux is regulated by a variety of environmental cues but the downstream signalling pathways are poorly defined, especially the way in which calcium regulates plasmodesmal closure. Here, we identify that closure of plasmodesmata in response to bacterial flagellin, but not fungal chitin, is mediated by a plasmodesmal‐localized Ca 2+ ‐binding protein Calmodulin‐like 41 (CML41). CML41 is transcriptionally upregulated by flg22 and facilitates rapid callose deposition at plasmodesmata following flg22 treatment. CML41 acts independently of other defence responses triggered by flg22 perception and reduces bacterial infection. We propose that CML41 enables Ca 2+ ‐signalling specificity during bacterial pathogen attack and is required for a complete defence response against Pseudomonas syringae .